Fibrin Modulates Shear-Induced NETosis in Sterile Occlusive Thrombi Formed under Haemodynamic Flow - Yu, Xinren; Diamond, Scott L. (Thrombosis and Haemostasis, 2019)
Neutrophils can release extracellular traps (NETs) in infectious, inflammatory and thrombotic diseases. NETs have been detected in deep vein thrombosis, atherothrombosis, stroke, disseminated intravascular coagulation and trauma. We have previously shown that haemodynamic forces trigger rapid NETosis within sterile occlusive thrombi in vitro. Here, we tested the effects of thrombin, fibrin and fibrinolysis on shear-induced NETosis by imaging NETs with Sytox Green during microfluidic perfusion of factor XIIa-inhibited or thrombin-inhibited human whole blood over fibrillar collagen (±tissue factor). For perfusions under venous pressure drops (19 mm Hg/mm-clot), thrombin generation did not alter the near-zero level of NET generation. In contrast, production of thrombin/fibrin led to a twofold reduction in neutrophil accumulation and a sixfold reduction in NET generation after 30 minutes of arterial perfusion (163 mm Hg/mm-clot). Exogenously added tissue type plasminogen activator (tPA) drove robust fibrinolysis; however, tPA did not trigger NETosis under venous flow. In contrast, tPA did enhance NET generation in clots subjected to arterial pressure drops. After 45 minutes of arterial perfusion, clots treated with 30 nM tPA had a threefold increase in total NET production and a twofold increase in normalized NET generation (measured as deoxyribonucleic acid:neutrophil) compared with fibrin-rich clots. Blocking fibrin polymerization resulted in similar level of NET release seen in tPA-treated clots, whereas ε-aminocaproic acid abolished the NET-enhancing effect of tPA. Therefore, fibrin suppresses NET generation and the absence of fibrin promotes NETs. We demonstrated that shear-induced NETosis was strongly inversely correlated with fibrin in sterile occlusive clots.
Keywords: extracellular traps; haemodynamics; fibrin; neutrophil; platelet